2013
DOI: 10.1525/sop.2013.56.4.647
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Recent Immigration on Serious Property Crime in Austin, Texas

Abstract: In this article the authors examine the impact of recent immigration on rates of serious property crime across communities in Austin, Texas. The greater Austin foreign-born population has increased by more than 580 percent since 1980, and Austin is considered a “preemerging” immigrant gateway city to the United States. The changing population dynamics in Austin provide an excellent opportunity to study the effect of recent immigration on crime in a target destination for recent immigrants. Although interest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…To measure residential instability, we use the average summed z scores for the following ACS variables: the percentage of the houses that are renter occupied and the percentage of people who lived in a different house 5 years ago (α = .80). Although using movement measured over 5 years may miss some movement, we use this measure as it is a common operationalization of residential instability in neighborhood crime research (Akins, Rumbaut, & Stansfield, 2009; Peterson & Krivo, 2010; Ramey, 2013; Stansfield, Akins, Rumbaut, & Hammer, 2013). Second, we controlled for the percentage of young males between the ages of 15 and 24.…”
Section: Methodsmentioning
confidence: 99%
“…To measure residential instability, we use the average summed z scores for the following ACS variables: the percentage of the houses that are renter occupied and the percentage of people who lived in a different house 5 years ago (α = .80). Although using movement measured over 5 years may miss some movement, we use this measure as it is a common operationalization of residential instability in neighborhood crime research (Akins, Rumbaut, & Stansfield, 2009; Peterson & Krivo, 2010; Ramey, 2013; Stansfield, Akins, Rumbaut, & Hammer, 2013). Second, we controlled for the percentage of young males between the ages of 15 and 24.…”
Section: Methodsmentioning
confidence: 99%
“…§20913(d)'s mandate that the Attorney General must apply the sex offender notification provisions as soon as feasible to offenders convicted before the statute was enacted is not consistent with giving immigration officials this kind of discretion. More importantly though, despite political arguments to the contrary, social scientific evidence indicates that immigrants commit no more crime than their U.S. born counterparts, and may commit fewer crimes (Chalfin & Deza, 2020;Diaz, 2011;Martinez, Lee, & Nielsen, 2006;Ousey & Kubrin, 2014;Stansfield et al, 2013;Vélez & Lyons, 2012). Even when they are victims of crime, immigrants, whether they are documented or undocumented, want little attention from the legal system (Bernat, 2019).…”
Section: Nielsen (2019) and Barton's (2020) Holdings Are Unjust Undermentioning
confidence: 99%
“…Sampson (2008) has observed that "cities of concentrated immigration are some of the safest places around" (p. 30). The inverse relationship between immigration and crime is also apparent in "new" immigrant gateways, such as Austin, where rates of both violent crime and serious property crime have declined despite high levels of new immigration (Akins et al, 2009;Stansfield et al, 2014). Some scholars suggest that new immigrants may revitalize dilapidated areas of cities, alleviating violent crime (Sampson, 2008).…”
Section: Immigration and Crime: Public Perceptions And Empirical Realmentioning
confidence: 99%